Teacher’s Teaching Quality in the Learning Process at SD Negeri 154 Palembang - Suarka, Suarka; Herdi, Hairani; Lestari, Ika (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to describe the teaching quality of teachers in the learning process at State Elementary School 154, Gandus District, Palembang City. This study uses a qualitative method. The informants in the research were school principals and teachers to improve the quality of learning at State Elementary School 154, Gandus District, Palembang City. Data collection in this research used interviews. The results of this research show that the quality of teachers teaching in the learning process at State Elementary School 154, Gandus District, Palembang City can be said to be good, the obstacles faced are lack of facilities and infrastructure, lack of funding allocation, strategies implemented to maximize resources so that the learning process can run. well and achieving learning objectives. Based on the findings from the research, it can be recommended that school managers allocate school funds appropriately so that infrastructure deficiencies can be overcome, as well as evaluate strategies that have been implemented for future improvements. The results of the research can be used as a reference and input for teachers and school management, especially regarding efforts to improve the quality of teachers in teaching.